Vertebral Coplanar Alignment Technique Versus Bilateral Apical Vertebral Derotation Technique in Neuromuscular Scoliosis. Issue 1 (January 2023) - Weissmann, Karen A.; Barrios, Carlos; Lafage, Virginie; Lafage, Renaud; Costa, Marcelo A.; Álvarez, Diego; Huaiquilaf, Carlos M.; Ang, Bryan; Schulz, Ronald G.
Study Design: Single-center retrospective analysis of prospectively collected data. Objective: Our aim was to compare the correction capacity in 3 planes of the VCA technique versus the AD technique in neuromuscular scoliosis patients. Methods: We analized patients with neuromuscular scoliosis that underwent posterior spinal fusion from 2013 to 2017 using 2 different techniques for correction: vertebral coplanar alignment (VCA) that takes into consideration the fact that the medial cortex is more resistant than the lateral cortex, with more anchor points for better distribution of forces and ligamentotaxis and the more widely spread apical derotation (AD) technique. Clinical, surgical, and radiographic information of patients operated on with the AD technique were compared to those operated on with the VCA technique in the coronal, sagittal and axial plane at pre-op, immediate post-op, and 2 year follow-up. Results: 64 patients met inclusion criteria, 34 patients underwent the VCA technique and 30 patients underwent the AD technique. The 2 cohorts did not differ in terms of demographics, clinical presentation or preoperative alignment. There were no significant differences in the correction ability between both techniques regarding curve magnitude, apical vertebral rotation, or pelvic obliquity. There was a significant decrease in thoracic kyphosis in the AD group compared to the VCA group in the immediate postop period (4.2 ± 26.6º for VCA and 13.2 ± 21.3º for AD (p = 0.048)). Conclusion: Both apical derotation technique and vertebral coplanar alignment allow for correction in the 3 planes for patients with neuromuscular scoliosis. VCA is a less hypokyphosing technique than AD.